Differential Scanning Calorimetry (DSC) and Synchrotron X-ray Diffraction Study of Unmilled and Milled LiBH4: A Partial Release of Hydrogen at Moderate Temperatures - J. Huot; T. Klassen; A. Gerhauser; Y. Filinchuk; J. Lang (Crystals, 2011)
A systematic investigation of phase transitions in unmilled and milled LiBH4 has been performed by Pressurized Differential Scanning Calorimetry (PDSC). It was found that a large exotherm is present below the low temperature (LT) → high temperature (HT) phase transition. This exotherm is not caused by air contamination but seems to originate from hydrogen release from a solid solution in the matrix of LiBH4 low temperature phase. The exotherm activation energy has been measured to be 100 kJ mol–1. Calorimetric measurements under argon and hydrogen have shown that for the milled sample, the endothermic peak of the LT → HT transition is split in two when the PDSC scan is performed under hydrogen atmosphere. Synchrotron X-ray powder diffraction on the milled LiBH4 sample revealed only a single-step transition from the LT to HT phase, both under vacuum and under 2 and 40 bar of hydrogen pressure. The axial ratios for the LT LiBH4 below 300 K are significantly altered by milling; they are also considerably different under 40 bar of hydrogen, indicating an interaction between the hydrogen gas and the LT LiBH4 solid phase.